Creating a Man for the Future: A Narrative Analysis of Male In-Migrants and Their Constructions of Masculinities in a Rural Context - Aure, Marit; Munkejord, Mai Camilla (Sociologia Ruralis, 2016)
Source at http://dx.doi.org/10.1111/soru.12111 Most research on rural masculinity focuses on sedentary and agricultural lifestyles. Based on fieldwork and interviews with 18 male newcomers, this article explores constructions of masculinities among in-migrants engaged in several occupations and entrepreneurial activities in Finnmark, in Northern Norway. Building on the concept of hegemonic masculinities, we show how a specific combination of compact geography, a changing labour market and the Nordic dual-earner family model and welfare state create a rural space of opportunities in which male in-migrants construct themselves as men for the future. The respondents emphasise the importance of intensive fatherhood, being a supportive spouse, and commitment to leisure activities as well as their professional identities. Contrary to studies of rural masculinities emphasising ‘macho’ traits, our analysis demonstrates the prevalence of novel nonhegemonic masculinities among in-migrants in northernmost Norway.